Promoting healthy lifestyle considerations during pregnancy in Midwifery clinics in China: a best practice implementation project. Issue 3 (28th September 2021) - Zhai, Jinguo; Hu, Xiaoqi; Wen, Zhiying; Chen, Lihua; Ye, Ranran; Zheng, Xiaozhu; Xiong, Anqi; Barker, Timothy H.; McArthur, Alexa
ABSTRACT: Objectives: The aim of this project was to initiate and promote formal and individualized evidence-based education on healthy lifestyle choices during pregnancy for pregnant women. Introduction: Evidence suggests that lifestyle choices during pregnancy can have a profound influence on many pregnancy complications and chronic diseases such as preterm birth, diabetes, obesity, fetal growth restriction, breast cancer and hypertensive diseases in both pregnant women and their babies. It is widely accepted that formal, individualized, hospital-directed education about lifestyle choices during pregnancy should commence as early as the first consultation between pregnant women and maternal healthcare workers. Methods: The methods of this project were audit and feedback. The approach to data collection used the Joanna Briggs Institute (JBI) Practical Application of Clinical Evidence System and implementation planning utilized the Getting Research into Practice component. A baseline audit of 50 observations of midwife-led education on prenatal lifestyle were conducted and measured against seven best practice audit criteria. Targeted strategies were then implemented to improve compliance to best practice. A follow-up audit was conducted over a 6-month period from June 2019 to November 2019. Results: The baseline audit revealed significant deficits between current prenatal education practice and recommended best practice. Zero percent compliance was observed in six out of seven audit criteria, indicating that education provided did not conform to best practice. Total compliance (100%) was observed for one audit criterion at baseline, assessing pregnant women being offered an opportunity to discuss and ask questions regarding the education session or information they had received. Three barriers that prevented midwives from achieving compliance with best practice were identified, and a bundled education strategy was implemented. A follow-up audit indicated 100% compliance of all audit criteria. Conclusion: Results demonstrated that formal, individualized, midwife-led prenatal education and provision of relevant evidence-based resources had an immediate positive effect. The project helped to transform care givers' attitudes toward education regarding lifestyle during pregnancy from a passive routine 'must do' task to an active process with focus on healthy lifestyle and engagement of pregnant women. Future strategies such as support from hospital management and social media are planned in conjunction with follow-up clinical audits to ensure sustainability.